1999
DOI: 10.1074/jbc.274.7.4036
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Involvement of Clusterin in Chicken Ovarian Follicle Development

Abstract: The interaction of the female germ cell with somatic cells during the development of the ovarian follicle in the chicken provides a prime system to study gene expression. Here, we have uncovered the involvement of clusterin, the function(s) of which is still poorly understood, in this complex process. As revealed by molecular cloning, chicken clusterin is a 428-residue protein that migrates at 70 kDa on SDS-polyacrylamide gel electrophoresis and possesses most of the structural features of its mammalian succes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(21 citation statements)
references
References 55 publications
2
18
0
Order By: Relevance
“…Previous work has shown that CLU and CLU-Ab complexes (specifically) can be cleared by receptor-mediated endocytosis, via the cell surface receptor megalin, and are degraded in lysosomes [21]. A number of other studies have also suggested that CLU and CLU-ligand complexes can be cleared by the same route [39,43]. Data presented here also strongly implicates the classical route of receptor-mediated endocytosis and lysosomal degradation in the clearance of CLU-client protein complexes.…”
Section: Discussionsupporting
confidence: 59%
“…Previous work has shown that CLU and CLU-Ab complexes (specifically) can be cleared by receptor-mediated endocytosis, via the cell surface receptor megalin, and are degraded in lysosomes [21]. A number of other studies have also suggested that CLU and CLU-ligand complexes can be cleared by the same route [39,43]. Data presented here also strongly implicates the classical route of receptor-mediated endocytosis and lysosomal degradation in the clearance of CLU-client protein complexes.…”
Section: Discussionsupporting
confidence: 59%
“…26 These complexes are removed by interaction with megalin (LRP-2) 41,42 and other receptors of the LDLR family. 43 Since exposition of hydrophobic residues of the Aβ:scFv-h3D6 complex has been reported, 12 it is tempting to propose that clusterin could have internalized the complex and, as a consequence, both clusterin and Aβ-oligomers would be decreased in the extracellular fraction of treated animals.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, and more generally, it is becoming clear that both yolk precursor receptors bind and transport nonlipoproteins to the yolk (e.g. Mac Lachlan et al, 1994;Mahon et al, 1999). Variation in yolk precursor receptor expression, as we have documented here, might therefore provide an important mechanism mediating inter-individual variation in 'maternal effects', i.e.…”
Section: Discussionmentioning
confidence: 83%